Sports injuries in Plus League volleyball players - Ciesla, E.; Dutkiewicz, R.; Mglosiek ,M.; Nowak-Starz, G.; Markowska, M.; Jasinski, P.; Dudek, J. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: Although physical activity brings a range of lifelong health benefits, it may also lead to injuries that pose a significant threat to health. It is particularly noticeable in people involved in professional sports where sport-related injuries commonly occur and are associated with intense exercise which aims to improve physical fitness. The article attempts to determine incidence of sports injuries reported by Plus League volleyball players, as well as to identify their most common types and causes.